2005
DOI: 10.1512/iumj.2005.54.2653
|View full text |Cite
|
Sign up to set email alerts
|

Dissipativity and Gevrey regularity of a Smoluchowski equation

Abstract: We investigate a Smoluchowski equation (a nonlinear FokkerPlanck equation on the unit sphere), which arises in modeling of colloidal suspensions. We prove the dissipativity of the equation in 2D and 3D, in certain Gevrey classes of analytic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…We can show, as claimed in [3], [4] that at any time t > 0 the solution is analytic in the space variable. The idea is to show, following [4] (based on [2], [10]), that the solution is in some Gevrey class of functions, defined by a parameter depending on time. This class is a subset of the set of real analytic functions on the sphere.…”
Section: Together With Poincaré Inequality Solving This Inequality Gsupporting
confidence: 76%
See 1 more Smart Citation
“…We can show, as claimed in [3], [4] that at any time t > 0 the solution is analytic in the space variable. The idea is to show, following [4] (based on [2], [10]), that the solution is in some Gevrey class of functions, defined by a parameter depending on time. This class is a subset of the set of real analytic functions on the sphere.…”
Section: Together With Poincaré Inequality Solving This Inequality Gsupporting
confidence: 76%
“…Following [4], we will show that the solution belongs to a special Gevrey class. We define the space G r , as the set of functions g (with mean zero) such that ∆…”
Section: A Appendixmentioning
confidence: 99%
“…Existence and uniqueness of solutions for (1.1) in L 2 or Sobolev H s spaces is a classical result. Combining a result of [4] and a method of [7], we show that for any initial condition q 0 in a measure class the (unique) solution q(t) of (1.1) is in a analytical functions space for all times t > 0. One consequence of the regularizing properties of equation (1.1) is that many convergence phenomena of solutions towards equilibria or invariant manifolds happen in an analytic-functions space and not just in the classical L 2 space.…”
Section: Introductionmentioning
confidence: 84%
“…For example, in [9] it has been shown that bounds on the analyticity radius can be employed to determine whether a given initial data lies near the global attractor. The technique introduced in [10] has been extended to the case of certain nonlinear parabolic equations in [7], and, very recently, to the Smoluchowski equation in [6]. The study of the space analyticity radius for the NSE and KSE in the setting of a Banach (L p ) space was first carried out by Grujić and Kukavica [16].…”
Section: The Kuramoto-sivashinsky Equation (Kse) Ismentioning
confidence: 99%